Risiko Kematian Pasien Covid-19 dan Faktor yang Memengaruhinya - Margareth Dwiyanti Simatupang; I Made Arcana (Seminar Nasional Official Statistics, 2021)
The number of cases of Coronavirus disease 2019 (Covid-19) in Indonesia has increased, which the percentage of increasing the number of cases in Sumatra is relatively higher than cases at national level. The rapid spreading of Covid-19 has affected to increasing the number of people being infected and died of Covid-19. This study aims to determine the characteristics of survival status of Covid-19 patients and factors affecting their death risk. The research was conducted at H. Adam Malik Hospital, as a referral hospital for Covid-19 patients, and an educational hospital. The research data was obtained from recording of the medical condition of Covid-19 patients in the period of March-October 2020. The statistical method used for data analysis was survival model, particularly the proportional hazard model applying the exponential distribution. The analysis results showed that Covid-19 patients with higher death risk occurred to male patients, having symptoms of dyspnea, comorbidities, and high severity.